Ineffective insurance in lower and middle income countries is an obstacle to universal health coverage - El-Sayed, Abdulrahman M (J Glob Health, 2018)
BACKGROUND: Recent health policy efforts have sought to promote universal health coverage (UHC) as a means of providing affordable access to health services to populations. However, insurance schemes are heterogeneous, and some schemes may not provide necessary services to those covered. We explored the prevalence and determinants of ineffective insurance across 42 lower and middle income countries (LMICs) from the 2002-2004 World Health Survey. METHODS: Respondents were defined as having ineffective health insurance if they reported being insured and: were forced to borrow or sell personal items to pay for health services; had an untreated chronic condition; or had recently delivered a child outside of a skilled health facility (women only). RESULTS: Among the insured, 13% had ineffective insurance, which was most commonly due to having to borrow or sell to pay for health care. The likelihood of ineffective insurance was lowest in upper-middle income countries and higher in other lower-middle and low-income countries. Ineffective insurance also decreased with family wealth and was higher among rural residents. CONCLUSIONS: Our findings suggest that a high proportion of insurance in LMICs is ineffective, particularly among those who need it most, and that attention should be paid to effectiveness when defining health insurance in policy conversations about UHC.